2004
DOI: 10.1557/proc-812-f7.7
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Analysis of Electromigration Lifetimes and Void Evolution for Cu Interconnects

Abstract: Electromigration (EM) failure statistics and the origin of the lognormal deviation (σ) for Cu interconnects have been investigated by analyzing the lifetime statistics and void size distributions at various stages during EM testing. Experiments were performed on 0.18 μm wide Cu interconnects with tests terminated after specific amounts of resistance increases, or after a specified test time. Void size distributions of resistance-based, as well as time-based EM tests were obtained using focused ion beam (FIB) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 50 publications
2
11
0
Order By: Relevance
“…At the end an abrupt resistance increase (for the 2:5I 0 case at 4.7Ms) leading to an open circuit failure can be observed. This observations are consistent with the resistance change measured in accelerated EM tests for dual damascene structures [10] and filled TSV structures [11].…”
Section: Resultssupporting
confidence: 89%
“…At the end an abrupt resistance increase (for the 2:5I 0 case at 4.7Ms) leading to an open circuit failure can be observed. This observations are consistent with the resistance change measured in accelerated EM tests for dual damascene structures [10] and filled TSV structures [11].…”
Section: Resultssupporting
confidence: 89%
“…SiN-and SiC-based films are widely used as capping materials for copper interconnects. It has been shown in several studies [5] …”
Section: The Etch Stop/copper Interfacementioning
confidence: 80%
“…If the temperature (or ) of the interconnect is time dependent, EM stress build-up can be derived as (detailed derivation can be found in [9], [20]) (5) If we assume that the stress build-up reaches a certain threshold ( ) at which an EM failure occurs, we have (6) where is a constant determined by the critical stress (i.e., ). If an average value of exists, we obtain a closed form for the time to failure (7) where is the expected value for , and is the temperature factor, as defined in (4), having the form , where is a constant.…”
Section: B Time-dependent Thermal Stressmentioning
confidence: 99%
“…Various experiments [6], [26] showed that, in Cu interconnect, voids tend to nucleate at the cathode end (near the via), and void growth is the dominant failure process because the critical mechanical stress for void nucleation in Cu is much smaller than that for aluminum. With spatial thermal gradients in the interconnect, it is possible that the location of void nucleation is no longer at the cathode end.…”
Section: A Em Model With Spatial Thermal Gradientsmentioning
confidence: 99%
See 1 more Smart Citation